Biodiversity of the philanthine wasps in the Middle Eastern and North African countries with special reference to the Egyptian fauna (Apoidea: Crabronidae: Philanthinae). (3rd April 2023) - Malash, Alyaa A.; Edmardash, Yusuf A.; Gadallah, Neveen S.
ABSTRACT: An updated checklist of the species of the subfamily Philanthinae in the Middle Eastern and North African countries with special reference to Egypt is provided here. The list includes 176 and 47 valid species and subspecies, respectively, in four genera: Cerceris (131 species, 38 subspecies), Philanthinus (3 species), Philanthus (27 species, 9 subspecies), and Pseudoscolia (15 species). Distributions, both in the Middle East and North Africa, and distributional maps are provided for each species whenever available. In Egypt, the subfamily Philanthinae is represented by 56 species, of which the presence of the following species is questionable and considered to be doubtful records: Cerceris dispar Dahlbom, C. leucochroa Schletterer, C. quadricincta (Panzer), C. schmiedeknechti Kohl, C. specularis A. Costa, Philanthus sulphureus F. Smith, and P. venustus (Rossi), and the two subspecies, P. triangulum diadema (Fabricius), and P. triangulum obliteratus Pic.